Managing A Crisis Situation In Sport – A Case Study Of Polish Clubs - Karolina ROGOWSKA (Communications of International Proceedings, 2022)
It is difficult to deny that the sports market has undergone deep commercialization and globalization processes. It is also impossible to disagree with the fact that in the last 5 years, professional sport in Poland has developed significantly. From an economic point of view, sport is business. There is no need to convince anyone that it plays a huge role on a micro and macro scale. The value of the Polish sports industry in 2018 was approximately PLN 10 billion. On the other hand, the related budget investments amounted to nearly PLN 1.8 billion. The data comes from the report of the Polish Economic Institute. In turn, the global sports market was worth almost half a trillion dollars in 2018 (Forbes, 2021). The aim of the article is to analyze the methods of managing a crisis situation in sport as a result of strategic changes in the sport, social, organizational and ownership dimensions. As part of the review of the case studies, an analysis of practical examples based on clubs from Poland was made.
Keywords: Management; Economy; Entrepreneurship; Sport; Business; Crisis Management.